ANALYSIS THE IMPLEMENTATION OF CONTEXTUAL BASED PROBLEM BASED LEARNING IN STRENGTHENING THE MATHEMATICAL CRITICAL THINKING OF LOWER GRADE - Hidayanti, Andina Nurnida; Supriyadi (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
The stagnation of critical thinking skills in elementary school students is often rooted in the gap between abstract mathematics curricula and the cognitive characteristics of students who are still in the concrete operational stage. Conventional teacher-centered methods exacerbate this condition, rendering students passive. This study aims to analyze the implementation of the Problem-Based Learning (PBL) model using contextual problems to strengthen students' mathematical critical thinking skills. Employing a descriptive qualitative approach, the research was conducted at SDN Cemengkalang with Grade III students as subjects. Data were collected through participant observation, interviews, and documentation, then analyzed using triangulation techniques. The results demonstrate that integrating real objects (such as wall clocks and floor tiles) within PBL stages effectively bridges students' thinking from concrete to abstract phases. Specifically, the focus indicator improved sharply as students became capable of filtering essential data from complex narrative problems. In the reasoning aspect, group discussion interactions encouraged students to shift from merely providing short answers to constructing evidence-based causal explanations regarding geometric properties. Meanwhile, inference skills were formed through independent conclusion-drawing, which was refined through iterative reflection processes. It is concluded that PBL successfully transforms students' roles from passive receivers into active knowledge constructors. Theoretically, these findings reinforce social constructivism theory, while practically recommending visual contextual problems as the primary scaffolding in lower-grade classes.